2012
DOI: 10.1021/jf2051653
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Total Type II Pyrethroid Pesticides in Citrus Oils and Water by Converting to a Common Product 3-Phenoxybenzoic Acid

Abstract: Pyrethroids are a class of insecticides that are becoming increasingly popular in agricultural and home use applications. Sensitive assays for pyrethroid insecticides in complex matrices are difficult with both instrumental and immunochemical methods. Environmental analysis of the pyrethroids by immunoassay requires either knowing which pyrethroids contaminate the source or the use of nonspecific antibodies with cross-reactivities to a class of compounds. We describe an alternative method that converts the typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…These might be because cyano-3-phenoxybenzyl alcohol was gradually oxidized to 3-phenoxybenzaldehyde and then to 3-PBA. 12 At 72 h, CY degradation and 3-PBA content reached 50.36% and 23.16 mg L −1 , respectively. Compared with other CY-degrading organisms, such as Pseudomonas IES-Ps-1 isolated by Jilani and Khan that could degrade 51% CY (80 mg L −1 ) in 48 h 22 and Bacillus sp.…”
Section: ■ Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…These might be because cyano-3-phenoxybenzyl alcohol was gradually oxidized to 3-phenoxybenzaldehyde and then to 3-PBA. 12 At 72 h, CY degradation and 3-PBA content reached 50.36% and 23.16 mg L −1 , respectively. Compared with other CY-degrading organisms, such as Pseudomonas IES-Ps-1 isolated by Jilani and Khan that could degrade 51% CY (80 mg L −1 ) in 48 h 22 and Bacillus sp.…”
Section: ■ Introductionmentioning
confidence: 93%
“…In the initial cultivation phase (0−24 h), the OD 600 value and CY degradation all exhibited rapid increase trends, and the CY degradation reached 23.35% at 24 h, whereas only 0.72 mg L −1 3-PBA was detected. This might be due to the fact that CY was first degraded into cyano-3-phenoxybenzyl alcohol by esterase produced by strain B-1, 12 and only a very small amount of cyano-3-phenoxybenzyl alcohol was transformed to 3-PBA. From 24 to 72 h, the CY degradation continued to increase, and the 3-PBA content began to increase quickly.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Beta-cypermethrin (β-CY) is an important pyrethroid pesticide, its residue can accumulate in the human body through the food supply chain and exhibit toxic effects on the human reproductive, immune, and nervous systems [46]. As a β-CY metabolite, 3-phenoxybenzoic acid (3-PBA) is difficult to degrade further in the environment due to its diphenyl oxide structure [7]. Heudorf et al [8] reported that 3-PBA residue in urine of children and adolescents in Germany was 0.30 μg/L.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, McCoy at al. 204 have developed a method based on HPLC/MS with an electrospray interface (ESI) to detect type II pyrethroids by converting them to 3-PBA. Also, GC-ECD was successfully employed for 3-PBA detection in water samples.…”
Section: -Phenoxybenzoic Acidmentioning
confidence: 99%
“…205 Alternative low-cost bioanalytical approaches have been reported. Traditional ELISA tests 204,206,207 for different matrices as well as fluorescence immunoassay have been developed. …”
Section: -Phenoxybenzoic Acidmentioning
confidence: 99%